Sequential proton boost after standard chemoradiation for high-grade glioma. Issue 2 (November 2017) - Adeberg, Sebastian; Bernhardt, Denise; Harrabi, Semi Ben; Uhl, Matthias; Paul, Angela; Bougatf, Nina; Verma, Vivek; Unterberg, Andreas; Wick, Wolfgang; Haberer, Thomas; Combs, Stephanie E.; Herfarth, Klaus; et al.
Abstract: Purpose: To retrospectively assess the feasibility and safety of a sequential proton boost following conventional chemoradiation in high-grade glioma (HGG). Method and materials: Sixty-six consecutive patients with HGG were treated with 50.0 Gy photons (50.0–50.4 Gy) in 2.0 Gy (1.8–2.0 Gy) fractions, followed by a proton boost with 10 Gy equivalent (Gy(RBE)) in 2.0 Gy(RBE) fractions. Patients were matched one to one with 66 patients with HGG undergoing conventional radiation therapy (RT) with 60.0 Gy photons (59.4–60.0 Gy) in 2.0 Gy fractions (1.8–2.0 Gy). Matching criteria were age, WHO grade, Karnofsky's performance status, PTV size, temozolomide therapy (each p > 0.1). The study assessed progression-free survival (PFS), overall survival (OS), acute treatment-related toxicity (CTCAE v.4.03) and pseudoprogression (RANO criteria). Results: Median PFS and OS were similar in both treatment groups (bimodality RT, PFS: 8.8 months [2–32 months], OS 19.1 months [4–41 months]; photon-only RT, PFS: 7.2 months [2–39 months], 20.9 months [3–53 months]; p = 0.430 and p = 0.125). The median PTV of the proton boost was significantly smaller than the photon plan PTVs (each p < 0.001). Acute toxicity was mild. Toxicity ≥grade 2 was observed in 6 patients (9%) receiving bimodality RT and 9 patients (14%) receiving photon-only RT. Two types of severe adverse events (CTCAE grade 3) occurred solely in the photon-only group: severe increase in intracranial pressure (5%); and generalized seizures (3%). Pseudoprogression was rare, occurring on average 6 weeks after radiotherapy, and was balanced in both treatment groups ( n = 4 each; 8%). Conclusion: Delivering a proton boost to significantly smaller target volumes when compared to photon-only plans, yielded comparable progression and survival rates at lower CTCAE grade 3 acute toxicity rates. Pseudoprogression occurred rarely and evenly distributed in both treatment groups. Thus, bimodality RT was at least equivalent regarding outcome and potentially superior with respect to toxicity in patients with HGG. Summary: Treating patients with HGG with 50.0 Gy photons in 2.0 Gy fractions, followed by a proton boost with 10 Gy(RBE) in 2.0 Gy(RBE) fractions, is safe and feasible. Severe radiation-induced acute toxicity and pseudoprogression were rare in both treatment groups. Therefore, in this clinical setting, combined proton radiotherapy might be beneficial in terms of further risk reduction for treatment-related side effects. Interestingly, treatment volume reduction using a proton boost led to comparable survival and progression rates with decreased severe treatment-related toxicity compared to conventional photon radiotherapy.